'As good as a chorus': Hamlet's Mousetrap in philosophy and psychoanalysis. Issue 9 (2nd September 2022) - Arribas, Sonia
ABSTRACT: A great part of Hamlet's mystery resides in the Mousetrap. Its role is fundamental for the tension of the play, yet its importance extends beyond that. Philosophers and psychoanalysts alike have been fascinated by it. The former have underlined its epistemological aspects and capacity for self-reflection: its power to mirror reality and reveal something new. The latter have placed weight on its 'primal scene' character and have underlined its failure to move Hamlet to act. Here I explore the paradox that results from putting philosophy and psychoanalysis together. To illustrate its functions, as well as the different readings of it, I delve into certain moments of the scene and Hamlet several times. Expanding on some remarks made by Lacan about the Mousetrap, I contend that it is a 'rigging system', a highly complex mise-en-abyme structure and intersubjective complex unfolded over successive layers. This explains the self-reflectivity discerned by philosophers. Following Benjamin and Lacan, and by means of a detour through Schmitt, I argue at the end that its failure needs to be situated in the historical moment when it was created – a world characterised by the lack of transcendent values – one in which art folds back upon itself infinitely.